Intrinsically Disordered Protein Analysis Volume 2, Methods and Experimental Tools - Uversky, Vladimir N.; Dunker, A. Keith; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Over the past decade, there has been an explosive development of research of intrinsically disordered proteins (IDPs), which are also known as unfolded proteins. Structural biologists now recognize that the functional diversity provided by disordered regions complements the functional repertoire of ordered protein regions. In Intrinsically Disordered Protein Analysis: Methods and Experimental Tools, expert researchers explore the high abundance of IDPs in various organisms, their unique structural features, numerous functions, and crucial associations with different diseases. Volume 2 includes sections on single molecule techniques, methods to assess protein size and shape, analyzing conformational behavior, mass-spectrometry, expression and purification of IDP’s. Written in the highly successful Methods in Molecular Biology™ series format, the chapters include the kind of detailed description and implementation advice that is crucial for getting optimal results in the laboratory. Thorough and intuitive, Intrinsically Disordered Protein Analysis: Methods and Experimental Tools helps scientists further their investigations of these fascinating and dynamic molecules.
Keywords: Proteins .; Protein Science; Protein Structure